AKULTURASI KEBUDAYAAN DAN PERAN PEREKONOMIAN ETNIS TIONGHOA DI KOTA SEMARANG 1950 - 1960 - Pino; Triwahana (Universitas PGRI Yogyakarta, 2023)
This research aims (1) to determine the acculturation of ethnic Chinese in the city of Semaramg, (2) to determine the economic role of ethnic Chinese in the city of Semarang, (3) to determine the differences between Chinatown in the city of Semarang and other cities. This research focuses on the Chinatown area in Semarang by using literature methods with steps: heuristics, verification or source criticism, there are two steps that need to be taken, namely external criticism and internal criticism. The next interpretation is a series of histories based on sequence and history. Compilation is compiling data obtained from sources into a scientific work according to the title. The results of the research concluded that the acculturation of ethnic Chinese in Semarang occurred due to exchanges between cultures without eliminating any of these cultures and became a history of the city of Semarang which is harmonious and harmonious between cultures, the role of ethnic Chinese in the economy, improving the local economy, creating jobs, and increasing power. Business competitiveness in Semarang, the differences between Semarang's Chinatown are in several aspects, namely, the geographical conditions are different from other cities, it is the first canalized city in Indonesia, the architecture, culture and traditions, community, and history of each Chinatown in Indonesia are different.